The stained-glass palm, geonoma epetiolata - Blanco Coto, Mario Alberto (2007)
Geonoma epetiolata is the only neotropical palm that exhibits substantial leaf mottling. This article provides a summary of its biology and conservation, some observations of natural populations and a discussion of the ecological role of leaf mottling.